The Construction of Indonesian Political Fiqh: Maqasid Al-Shariah Perspective and Ahmad Ar-Raisuni’s Thoughts - Syaiful Bahri (Justicia Islamica, 2020)
Some issues in various classical political fiqh literature are irrelevant if applied in the current context. This paper discusses how important the reconstruction and renewal of several classical political fiqh issues are adapted to the plural Indonesian context. In this study, the author uses the Maqasid al-Shariah theory and Ahmad ar-Raisuni’s thinking, specifically addressing political issues as the mainframe of analysis. By conducting a library study, this study concludes that several classical political fiqh issues are indeed irrelevant to the times, and therefore need to be updated and reviewed. In addition, this study has also resulted in a new construction of Indonesian political fiqh formulated in four crucial issues: democracy, state format, criteria for leaders in Indonesia, and application of Islamic Law (Shariah).